Forgotten Exile : The Deportations of Azerbaijanis by the Armenians in the Caucasus during the Twentieth Century - Gunter, Michael M., (Middle East and Islamic Studies E-Books Online, Collection 2025., 2025)
A significant part of our original primary sources derive from the personal remembrances of Ali Askerov, one of the two authors of this book. He is an ethnic Azerbaijani scholar who was born and lived in an area of present-day Armenia during the first part of his life. He was forced to leave his place of birth at the age of 18 in July 1988. Indeed, his family, as did several hundred thousand other Azerbaijanis, had lived in these places for many centuries, but were deported into exile or ethnically cleansed during the twentieth century by the Armenians. The Armenians did this to create an ethnically homogenous area in which they could create their own ethnically-based Armenian state. In addition to Professor Askerov's detailed remembrances, this book is based on primary archival material and interviews obtained from sources in contemporary Armenia, Azerbaijan, and elsewhere as well as a variety of secondary sources written by Azerbaijanis, Armenians, and many others.